The Association of Iron and the Pathologies of Parkinson’s Diseases in MPTP/MPP+-Induced Neuronal Degeneration in Non-human Primates and in Cell Culture - Shi, Liangqin; Huang, Chao; Luo, Qihui; Rogers, Edmond; Xia, Yu; Liu, Wentao; Ma, Wenjing; Zeng, Wen; Gong, Li; Fang, Jing; Tang, Li; Cheng, Anchun; et al. (Frontiers in Aging Neuroscience, 2019)
Despite much efforts in the last few decades, the mechanism of degeneration of dopamine (DA) neurons in the substantia nigra (SN) in Parkinson’s disease (PD) remains unclear. This represents a major knowledge gap in idiopathic and genetic forms of PD. Among various possible key factors postulated, iron metabolism has been widely suggested to be involved with fueling oxidative stress, a known factor in the pathogenesis of PD. However, the correlation between iron and DA neuron loss, specifically in the SN, has not been described in experimental animal models with great detail, with most studies utilizing rodents and, rarely, non-human primates. In the present study, aiming to gain further evidence of a pathological role of iron in PD, we have examined the correlation of iron with DA neuron loss in a non-human primate model of PD induced by MPTP. We report a significant iron accumulation accompanied by both DA degeneration in the SN and motor deficits in the monkey that displayed the most severe PD pathology and behavioral deficits. The other two monkeys subjected to MPTP displayed less severe PD pathologies and motor deficits, however, their SN iron levels were significantly lower than controls. These findings suggest that high iron may indicate and contribute to heightened MPP+-induced PD pathology in late or severe stages of PD, while depressed levels of iron may signal an early stage of disease. Similarly, using a cell culture preparation, we have found that high dose of ferric ammonium citrate (FAC), a factor known to enhance iron accumulation, increased MPP+-induced cell death in U251 and SH-SY5Y cells, and even in control cells. However, at low dose FAC restored or increased the viability of U251 and SH-SY5Y cells in the absence or presence of MPP+. These observations imply that high levels of iron likely contribute to or heighten MPP+ toxicity in the later stages of PD. While we report reduced iron levels in the earlier stages of MPTP induced PD, the significance of these changes remains to be determined.